Freezing and thawing effects on fat, protein, and lactose levels of human natural milk administered by gavage and continuous infusion - Andrea D. Abranches; Fernanda V.M. Soares; Saint-Clair G. Junior; Maria Elisabeth L. Moreira (Elsevier, 2014)
Objectives: to analyze the changes in human milk macronutrients: fat, protein, and lactose in natural human milk (raw), frozen and thawed, after administration simulation by gavage and continuous infusion. Method: an experimental study was performed with 34 human milk samples. The infrared spectrophotometry using the infrared analysis equipment MilkoScan Minor® (Foss, Denmark) equipment was used to analyze the macronutrients in human milk during the study phases. The analyses were performed in natural (raw) samples and after freezing and fast thawing following two steps: gavage and continuous infusion. The non-parametric Wilcoxon test for paired samples was used for the statistical analysis. Results: the fat content was significantly reduced after administration by continuous infusion (p < 0.001) during administration of both raw and thawed samples. No changes in protein and lactose content were observed between the two forms of infusion. However, the thawing process significantly increased the levels of lactose and milk protein. Conclusion: the route of administration by continuous infusion showed the greatest influence on fat loss among all the processes required for human milk administration. Resumo: Objetivo: analisar as alterações dos macronutrientes gordura, proteína e lactose no leite humano natural, congelado e descongelado, após a simulação da administração da dieta por gavagem e infusão contínua. Método: foi conduzido um estudo experimental com 34 amostras de leite humano. Foi utilizada a técnica da espectofotometria infravermelha (Milko Scan Minor®) para analisar os macronutrientes do leite humano nas etapas do estudo. As amostras foram analisadas na forma natural (crua) e após congelamento e descongelamento rápido nas duas formas de infusão: gavagem e infusão contínua. Foi usado o teste não paramétrico de Wilcoxon para amostras pareadas na análise estatística. Resultado: a gordura apresentou redução significativa após administração por infusão contínua (p < 0,001), tanto durante administração na forma natural quanto na forma descongelada. Não houve alteração da proteína e lactose segundo forma de infusão no leite descongelado e no leite in natura. O processo de descongelamento aumentou significativamente os níveis de lactose e de proteína do leite. Conclusão: a via de administração por infusão contínua foi o procedimento que mais influenciou na perda de gordura, dentre todos os processos necessários para administração do leite humano. Keywords: Human milk, Nutrition, Newborn, Palavras-chave: Leite humano, Nutrição, Recém-nascido